Early CNS neurodegeneration in radiologically isolated syndrome. Issue 3 (June 2015) - Azevedo, Christina J.; Overton, Eve; Khadka, Sankalpa; Buckley, Jessica; Liu, Shuang; Sampat, Mehul; Kantarci, Orhun; Lebrun Frenay, Christine; Siva, Aksel; Okuda, Darin T.; Pelletier, Daniel
Abstract : Objective: Increasing evidence indicates that the thalamus may be a location of early neurodegeneration in multiple sclerosis (MS). Our objective was to identify the presence of gray matter volume loss and thinning in patients with radiologically isolated syndrome (RIS). Methods: Sixty-three participants were included in this case-control study. Twenty-one patients with RIS were age- and sex-matched to 42 healthy controls in a 1:2 ratio. All participants underwent brain MRIs on a single 3T scanner. After lesion segmentation and inpainting, 1 mm 3 -isometric T1-weighted images were submitted to FreeSurfer (v5.2). Normalized cortical and deep gray matter volumes were compared between patients with RIS and controls using t tests, and thalamic volumes were correlated with white matter lesion volumes using Pearson correlation. Exploratory cortical thickness maps were created. Results: Although traditional normalized total gray and white matter volumes were not statistically different between patients with RIS and controls, normalized left (0.0046 ± 0.0005 vs 0.0049 ± 0.0004, p = 0.006), right (0.0045 ± 0.0005 vs 0.0048 ± 0.0004, p = 0.008), and mean (0.0045 ± 0.0005 vs 0.0049 ± 0.0004, p = 0.004) thalamic volumes were significantly lower in patients with RIS (n = 21, mean age 41.9 ± 12.7 years) than in controls (n = 42, mean age 41.4 ± 11.2 years). Thalamic volumes correlated modestly with white matter lesion volumes (range: r = −0.35 to −0.47). Conclusion: Our data provide novel evidence of thalamic atrophy in RIS and are consistent with previous reports in early MS stages. Thalamic volume loss is present early in CNS demyelinating disease and should be further investigated as a metric associated with neurodegeneration.